Analysis of Determinants That Influence the Profitability of Conventional Banks in Indonesia - Astari, Anindya; Rejekiningsih, Tri Wahyu (ARMADA : Jurnal Penelitian Multidisiplin, 2024)
This research aims to examine the factors that influence the level of profitability in conventional banking in Indonesia in 2010-2019. This research uses Return on Assets (ROA) as a ratio to describe the level of profitability of commercial banks in Indonesia. The object of this research is conventional banking in Indonesia, with a research sample of 6 groups of conventional banks, namely Persero Banks, Foreign Exchange Private Banks, Non-Foreign Exchange Private Banks, Regional Development Banks (BPD), Joint Venture, and Foreign Banks. The analytical method used in this research is panel data regression analysis with Random Effect Model (REM). The research shows that the spread interest rate, Bank Indonesia Certificate (SBI), and third party funds (DPK) have a positive and significant effect on Return on Assets (ROA). Meanwhile, the interbank liability variable has a negative and significant effect on Return on Assets (ROA). Simultaneously, spread interest rate, SBI, third party funds, and interbank liabilities influence ROA.